5 Discourse and Human Securities in Tewa Origins. Issue 1 (16th May 2016) - Ortman, Scott G.
ABSTRACT: For the Archaeology of Human Experience to have an impact on public policy, archaeologists need to identify what contemporary society values, determine the extent to which ancient societies provided these values, and examine what it was that enabled certain societies to provide them better than others. I develop a case study of this approach focusing on the famous "collapse" of Mesa Verde society and subsequent formation of ancestral Tewa society in the 13th century C.E. I translate the archaeological record into measures that reflect the United Nations Development Programme's dimensions of human security to show that ancestral Tewa society eventually met basic human needs better than Mesa Verde society had done. I also present archaeological, linguistic, and cultural evidence that argues the ultimate driver of enhanced security was conceptual change during the migration period. This example suggests ideas play important roles in structuring behavioral habits and thus long‐term social outcomes.